Comprehensive analysis platform to understand, remedy, and eliminate amyotrophic lateral sclerosis (CAPTURE ALS): Study protocol for a Canadian multicenter, multimodal, longitudinal observational study - Natalie Saunders; Claire Magnussen; HyungMo Kang; Mathieu Blais; Harpreet Bhinder; Gerald Pfeffer; Shelagh K. Genuis; Liziane Bouvier; Tanushka Anand; Rida Abou-Haidar; Agessandro Abrahao; Marie-Noëlle Boivin; et al. (PLoS ONE, 2025)
Background The marked heterogeneity of Amyotrophic Lateral Sclerosis (ALS) combined with a lack of biomarkers are key contributing factors to the lack of disease-modifying treatments. The Comprehensive Analysis Platform to Understand Remedy and Eliminate ALS (CAPTURE ALS) is a Canadian platform designed to create the most comprehensive picture of people living with ALS with the objective of facilitating ALS research initiatives worldwide. Objectives The main aims of CAPTURE ALS include: (1) to characterize ALS and healthy controls with biosamples and data in order to provide the most comprehensive picture of individuals living with ALS to date; (2) to create a de-identified database and biosample repository linked to detailed clinical information; and (3) to develop and implement an inclusive and transparent participant engagement strategy to be active throughout all stages of CAPTURE ALS. Methods/Results CAPTURE ALS is a prospective, multicenter, observational, longitudinal study. People living with ALS, or a related disease and healthy controls undergo a harmonized protocol including the collection of detailed clinical information, neurological and cognitive examination, speech recording, advanced magnetic resonance imaging, and biosampling. Data and samples are stored in a biobank operating under an open science governance framework. An inclusive and transparent participant engagement strategy was designed and implemented throughout all stages of CAPTURE ALS. Four sites are operating in the consortium with a fifth being onboarded. The target enrollment is 120 affected participants and 50 controls, with the first participant visit having occurred in March 2022. Recruitment is ongoing. Discussion CAPTURE ALS is a scalable clinical research platform that connects scientists and patients to facilitate efficient translational research. The unique and deeply phenotyped data and biosamples are a global resource towards the development of biomarkers and understanding ALS biology. This study is registered at clinicaltrials.gov (NCT: NCT05204017).